Pengaruh Pemberian Ekstrak Teh Hijau (Camellia sinensis L.) terhadap Penurunan Kadar Kolesterol Total Tikus Wistar (Rattus Norvegicus) Diabetes Induksi Aloksan - Zufarisky Sarel; Kristina Simanjuntak (Poltekkes Kemenkes Padang, 2020)
Green Tea works as an anti-dyslipidemia due to chronic hyperglycemia of diabetes through its flavonoid content. The purpose of this study was to determine the effectiveness of green tea extracts on reducing the total cholesterol levels of alloxan-induced diabetes Wistar rats. The study design uses true experimental. Samples were 30 Wistar strain male white rats, aged 8-12 weeks, weighing ±200 grams. Green tea extract doses of 200, 400, and 800 mg/kg body weight, and negative controls were given alloxan, and positive controls were given simvastatin. The treatment group except the normal group was injected with a dose of 125 mg/kg alloxan intraperitoneally and a high-fat feed. After 3 days blood from the tail was measured glucose using a glucometer and cholesterol with a spectrophotometer λ=546 nm, giving green tea extract for 16 days orally, then re-measuring blood cholesterol from the tail. The One Way Anova Test results show the effectiveness of green tea extract on reducing total cholesterol (p=0,000). The results of the Post-Hoc Bonferroni test giving green tea extract at a dose of 400 mg/kg were comparable to simvastatin (p=0.453) which best decreased total cholesterol levels close to normal values.